2006
DOI: 10.1101/gad.1459706
|View full text |Cite
|
Sign up to set email alerts
|

The bHLH-PAS protein Spineless is necessary for the diversification of dendrite morphology of Drosophila dendritic arborization neurons

Abstract: Dendrites exhibit a wide range of morphological diversity, and their arborization patterns are critical determinants of proper neural connectivity. How different neurons acquire their distinct dendritic branching patterns during development is not well understood. Here we report that Spineless (Ss), the Drosophila homolog of the mammalian aryl hydrocarbon (dioxin) receptor (Ahr), regulates dendrite diversity in the dendritic arborization (da) sensory neurons. In loss-of-function ss mutants, class I and II da n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 49 publications
1
105
1
1
Order By: Relevance
“…4,64 Sensory neuron dendrite patterning is defined by the combinatorial activities of a group of transcription factors, including the homeodomain factor Cut (homolog of Cux1 and 2), the BTB-domain factors Abrupt and Lola, the Kr€ uppellike factor Dar1, the Iroquois factor Mirror, the bHLH-PAS factor Spineless, the PRDM factor Hamlet, and the EBF factor Knot. 41,[68][69][70][71][72][73][74][75][76][77][78] These studies have demonstrated that individual transcription factors control specific aspects of dendrite cytoskeleton organization; for example, Cut and Lola were shown to regulate actin organization, 41,76,78 while Knot, Dar1, and Abrupt regulate microtubule organization. 20,41,77 A complex interacting network of microtubule regulatory events occurs within the differentiating neuron, 7 and consequently, a microtubule regulator that is an effector of a transcription factor need not be under the direct transcriptional control of that factor.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…4,64 Sensory neuron dendrite patterning is defined by the combinatorial activities of a group of transcription factors, including the homeodomain factor Cut (homolog of Cux1 and 2), the BTB-domain factors Abrupt and Lola, the Kr€ uppellike factor Dar1, the Iroquois factor Mirror, the bHLH-PAS factor Spineless, the PRDM factor Hamlet, and the EBF factor Knot. 41,[68][69][70][71][72][73][74][75][76][77][78] These studies have demonstrated that individual transcription factors control specific aspects of dendrite cytoskeleton organization; for example, Cut and Lola were shown to regulate actin organization, 41,76,78 while Knot, Dar1, and Abrupt regulate microtubule organization. 20,41,77 A complex interacting network of microtubule regulatory events occurs within the differentiating neuron, 7 and consequently, a microtubule regulator that is an effector of a transcription factor need not be under the direct transcriptional control of that factor.…”
Section: Microtubule Nucleation Control For Dendrite Morphogenesismentioning
confidence: 99%
“…This stereotypy suggests a genetic basis, and has led to experimental approaches to identify molecular regulators of dendrite development and morphology. In this article, we discuss new data published by Kim et al (2006) in this issue of Genes & Development on the role of the Spineless (Ss) basic helix-loop-helix-PAS (bHLH-PAS) transcription factor in controlling dendrite morphogenesis, as well as review the contributions of other regulatory proteins.…”
mentioning
confidence: 99%
“…1H ). Furthermore, neuronal type-specific markers, including Knot (Hattori et al, 2007;Jinushi-Nakao et al, 2007), Cut (Grueber et al, 2003), Abrupt (Sugimura et al, 2004), and Spineless (Kim et al, 2006), were expressed appropriately in dar1 Ϫ / Ϫ da neurons (Fig. 1I and data not shown).…”
Section: Dar1 Is Required For Multipolar Morphology In Postmitotic Nementioning
confidence: 99%
“…1 A, B). As a comparison, other transcription factors known to regulate dendritic development in multidendritic (md) neurons, such as Knot, Cut, Abrupt, and Spineless, are expressed either in a subset of or in all PNS and CNS neurons (Grueber et al, 2003;Sugimura et al, 2004;Kim et al, 2006;Hattori et al, 2007;Jinushi-Nakao et al, 2007;Crozatier and Vincent, 2008 and data not shown). The unique and selective expression of Dar1 in multipolar neurons led us to hypothesize that Dar1 determines the multipolar layout of neuronal dendrites.…”
Section: Dar1 Is Required For Multipolar Morphology In Postmitotic Nementioning
confidence: 99%
See 1 more Smart Citation